Choice of Law for Child Custody in Indonesia’s Mixed Marriages: A Best-Interests-Anchored Cascade - I Nyoman Sujana; Ni Nyoman Sri Puspadewi (International Journal of Law and Society, 2026)
Indonesia has no codified private international law rule identifying which law governs child custody when a mixed marriage dissolves, so courts default to the lex fori. This gap converts choice-of-law questions into status-denial problems, as illustrated by the District Court of Tabanan Decision No. 375/Pdt.G/2019/PN.Tab., where the resolution of marital validity extinguished the paternal relationship altogether. This article develops a normative model to determine the applicable law governing child custody in Indonesia, anchored in the best interests of the child. Using normative (doctrinal) legal research with statute, conceptual, case, and comparative approaches, primary, secondary, and tertiary legal materials were analyzed through grammatical, systematic, teleological, and constitutional interpretation. The analysis shows that Indonesian practice conflates the preliminary question of marital validity with custody, producing outcomes that are vertically inconsistent with the 1945 Constitution and horizontally inconsistent with the Child Protection and Human Rights Laws. Because lex loci celebrationis governs only the formal validity of marriage, it cannot properly govern custody. The article proposes a Best-Interests-Anchored Cascade: custody is characterized as an autonomous connecting category; the child's habitual residence serves as the primary connecting factor; lex patriae applies only subsidiarily; and public order operates as a narrow shield that may never extinguish filiation. The model offers courts an operable decision sequence and legislators a drafting template for a future Indonesian private international law statute.